2022
DOI: 10.3390/su142315909
|View full text |Cite
|
Sign up to set email alerts
|

Fast 1-D Velocity Optimization Inversion to 3D Velocity Imaging: A Case Study of Sichuan Maerkang Earthquake Swarm in 2022

Abstract: To obtain an accurate one-dimensional velocity model, we developed the EA_VELEST method based on the evolutionary algorithm and the VELEST program. This method can quickly generate a suitable 1D velocity model and finally input it into the 3D velocity inversion process using the TomoDD method. We adopt TomoDD methods to inverse the high-resolution three-dimension velocity structure and relative earthquake hypocenters for this sequence. This system processing flow was applied to the Sichuan Maerkang earthquake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(57 reference statements)
1
0
0
Order By: Relevance
“…Its horizontal location was at the intersection of the Lenglongling fault and Tuolaishan fault. The earthquake location results of this paper are consistent with those of other researchers [ 51 , 52 , 53 ]. The depth of the M s 5.1 aftershock at 2:9 on 8 January was 13.3 km, which indicated that the fault slip continued to extend and develop at deeper depths after the mainshock.…”
Section: Methodssupporting
confidence: 93%
“…Its horizontal location was at the intersection of the Lenglongling fault and Tuolaishan fault. The earthquake location results of this paper are consistent with those of other researchers [ 51 , 52 , 53 ]. The depth of the M s 5.1 aftershock at 2:9 on 8 January was 13.3 km, which indicated that the fault slip continued to extend and develop at deeper depths after the mainshock.…”
Section: Methodssupporting
confidence: 93%